2019
DOI: 10.1002/csr.1732
|View full text |Cite
|
Sign up to set email alerts
|

Green human resource management and job pursuit intention: Examining the underlying processes

Abstract: The present study was conducted with an objective to illuminate the complex psychological mechanisms underlying the relationship of green human resource management (GHRM) with job pursuit intention (JPI) of potential applicants. Specifically, a sequential mediation model linking GHRM with JPI through organizational prestige (OP) and organizational attractiveness (OA) was proposed using arguments from theories of signaling and social identity. A sample of 172 students enrolled in the final year of a Bachelors i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
84
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(91 citation statements)
references
References 37 publications
7
84
0
Order By: Relevance
“…We use undergraduate students enrolled in management degrees, who serve as potential managers. Although the use of students has been questioned, prior literature considers that using alumni as subjects is adequate for measuring managerial decisions (e.g., Chaudhary, 2019; Christensen & Kohls, 2003; Harrison & List, 2004) and environmental decisions (e.g., De la Torre et al, 2015; Rikhardsson & Holm, 2008; Sciarelli, Tani, Landi & Turriziani, 2020). In fact, numerous studies based on greenwashing have used undergraduate students as subjects (e.g., de Vries et al, 2015; Nyilasy, Gangadharbatla, & Paladino, 2014).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We use undergraduate students enrolled in management degrees, who serve as potential managers. Although the use of students has been questioned, prior literature considers that using alumni as subjects is adequate for measuring managerial decisions (e.g., Chaudhary, 2019; Christensen & Kohls, 2003; Harrison & List, 2004) and environmental decisions (e.g., De la Torre et al, 2015; Rikhardsson & Holm, 2008; Sciarelli, Tani, Landi & Turriziani, 2020). In fact, numerous studies based on greenwashing have used undergraduate students as subjects (e.g., de Vries et al, 2015; Nyilasy, Gangadharbatla, & Paladino, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…We use undergraduate students enrolled in management degrees, who serve as potential managers. Although the use of students has been questioned, prior literature considers that using alumni as subjects is adequate for measuring managerial decisions (e.g., Chaudhary, 2019;Christensen & Kohls, 2003;Harrison & List, 2004) Fritzche and Becker (1983). Both studies present a variety of ethical dilemmas, where a marketing executive was involved in a personal business venture that conflicts with the company's responsibilities.…”
Section: Participants and Samplementioning
confidence: 99%
“…Various scholars have identified the effects of this novel paradigm on multiple organizational and employee outcomes and found that green HRM is the foundation of getting competitive advantage and attracting quality employees. For example Khan and Noorizwan Muktar [30] performed empirical study on Malaysian students and found that green HRM is a source of attracting talented candidates, Chaudhary [44] tested a serial mediation model in which green HRM affected students intention to join green firms, Kim, Kim [45] from the employee centered approach studied green HR and found that it positively effects environmental performance and employee green behavior. Saeed, Afsar [46] confirmed that green HRM effects pro environmental behaviors of employees.…”
Section: Effects Of Green Hrm: An Overviewmentioning
confidence: 99%
“…Pham, Tučková [75] The results exposed that green training improve employee green behavior. Moreover, the interaction effect on organizational citizenship behavior depend on training, employee involvement and performance management Chaudhary [44] The study performed sequential mediating of OA and OP on JPI. Findings revealed that Green HRM practices positively impacts JPI with significant effect of serial mediation Silva Marco Antonio Batista, Costa Priscila Rezende [76] The study exposed that in order to improve environmental sustainability in the organizations and to meet environmental goals, green/ environmental training is imperative Al Kerdawy [77] The study exposed that the interaction effect of CSEV positively related to the effect of Green HRM on CRS in organizations and both green HRM and organizational support positively impacts CSR Chaudhary [78] The study was conducted from the perspective of students and environmental orientation was found to have positive interaction effect with Green HRM and job pursuit intention.…”
Section: Rq1: Dimensions/concepts/reflections Of Green Hrm Authormentioning
confidence: 99%
See 1 more Smart Citation